2021
DOI: 10.2196/29044
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Sensor-Controlled Digital Game for Heart Failure Self-management: Randomized Controlled Trial

Abstract: Background Poor self-management of heart failure (HF) contributes to devastating health consequences. Our innovative sensor-controlled digital game (SCDG) integrates data from sensors to trigger game rewards, progress, and feedback based on the real-time behaviors of individuals with HF. Objective The aim of this study is to compare daily weight monitoring and physical activity behavior adherence by older adults using an SCDG intervention versus a senso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Current digital health interventions with unobtrusive monitoring capabilities allow the gathering of relevant contextual data to tailor and adapt interventions without overburdening participants through cumbersome data collection [ 59 ]. This study protocol was informed by our feasibility randomized controlled trial study, in which we demonstrated the remote implementation of a smartphone-based intervention using a digital game and sensors among participants in 18 counties in Texas and Oklahoma [ 29 ]. Combining digital games and sensors holds the potential to offer a powerful way to improve treatment adherence [ 60 , 61 ]; sustain healthy behaviors; and make health care more participatory, personalized, predictive, and preventive, as defined by precision medicine [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Current digital health interventions with unobtrusive monitoring capabilities allow the gathering of relevant contextual data to tailor and adapt interventions without overburdening participants through cumbersome data collection [ 59 ]. This study protocol was informed by our feasibility randomized controlled trial study, in which we demonstrated the remote implementation of a smartphone-based intervention using a digital game and sensors among participants in 18 counties in Texas and Oklahoma [ 29 ]. Combining digital games and sensors holds the potential to offer a powerful way to improve treatment adherence [ 60 , 61 ]; sustain healthy behaviors; and make health care more participatory, personalized, predictive, and preventive, as defined by precision medicine [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The design of the game was guided by behavioral change mechanisms using the concepts of motivation, ability, and trigger from the Fogg behavioral model and self-determination theoretical frameworks, as described in detail in a previous study [ 33 ]. This app has already been developed by a multidisciplinary team and tested through initial usability and feasibility studies and is described in detail elsewhere [ 28 , 29 ]. Several screenshots from the SCDG are pictured in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, 13 RCTs offered rehabilitation as part of the intervention [64,75,80,82,147,149,151,152,157,160,163,169,178]. mHealth solutions (eg, telephone calls, text messages, and apps) were primarily used in 56 RCTs [53,56,57,59,63,67,69,78-80, 83-86,90,92,93,96,99,101,102,105,108,110,112-115,119, 120,124,128-130,134,136,140-142,146-148,150,155,157,161,163, 164,167,168,172,176,177,179,181,185], whereas 22 RCTs [58,60,61,65,70,81,87,111,116,117,126,133,134,145,149,151,154,156,165,171,173,174] used mHealth combined with a device (eg, wearable, pedometer, activity tracker, or Bluetooth-connected pulse oximeter or glycosometer). Furthermore, 6 RCTs [75,89,118,158,169,183]…”
Section: Intervention Componentsmentioning
confidence: 99%